Human-Computer Interaction for Development (HCI4D): The Southern African Landscape - (:unkn) unknown (My University, 2019)
Human-Computer Interaction for Development (HCI4D) research aims to maximise the usability of interfaces for interacting with technologies designed specifically for under-served, under-resourced, and under-represented populations. In this paper, we provide a snapshot of Southern African HCI4D research against the background of the global HCI4D research landscape. We commenced with a systematic literature review of HCI4D (2010–2017) then surveyed Southern African researchers working in the area. The contribution is to highlight the context-specific themes and challenges that emerged from our investigation.
Keywords: African Research